1990
DOI: 10.1111/j.1365-2265.1990.tb03882.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Urinary 6‐sulphatoxymelatonin, a Major Melatonin Metabolite, in Normal Human Subjects

Abstract: 6-Sulphatoxymelatonin (aMT6s) has been measured, by a direct radioimmunoassay, in urine from 130 normal volunteers aged 2-80 years. Its relationship to a number of physiological parameters has been assessed. Total urinary excretion of aMT6s did not vary in a group of 40 children aged 2-20 years (24 boys and 16 girls) except when expressed as a function of body weight. In this case, total aMT6s excretion over 24 h decreased as a function of age. In 90 adult volunteers (44 men and 46 women) aged 20-80 years, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
63
0
3

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 28 publications
9
63
0
3
Order By: Relevance
“…In a postmortem study of 33 cases Schmid et al (32) did not find a correlation between calcium deposits in human pineal gland but a negative correlation between calcium supernatant and the nighttime melatonin of pineal glands. Bojkowski and Arendt (35) did not find a correlation between 6-sulfatoxymelatonin (the urinary excretional form of melatonin) and pineal calcifications as detected by lateral skull x-ray. Kunz et al (36) used a semiquantitative approach to analyze CT slices (4 mm thickness).…”
Section: Discussionmentioning
confidence: 88%
“…In a postmortem study of 33 cases Schmid et al (32) did not find a correlation between calcium deposits in human pineal gland but a negative correlation between calcium supernatant and the nighttime melatonin of pineal glands. Bojkowski and Arendt (35) did not find a correlation between 6-sulfatoxymelatonin (the urinary excretional form of melatonin) and pineal calcifications as detected by lateral skull x-ray. Kunz et al (36) used a semiquantitative approach to analyze CT slices (4 mm thickness).…”
Section: Discussionmentioning
confidence: 88%
“…Firstly, the size of pineal calcification is not associated with melatonin secretion (Bojkowski and Arendt 1990;Commentz et al 1986). This is in line with the lack of association between the size of pineal calcification and pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally stated that no correlation can be demonstrated between the occurrence of pineal calcification and a reduced melatonin production (Arendt 1995). But, the two studies frequently cited in that context used predominantly skull X-ray, which provides only little information on the quantity of calcification-density and no information about the size of the remaining non-calcified tissue (Bojkowski and Arendt 1990; Commentz et al 1986).The adult shape and size of the pineal gland are, presumably genetically, determined early in life and reach their final stage around the first year of life (Wetterberg et al 1983;Schmidt et al 1995). The weight and dimensions are highly variable-up to a 20-fold inter-individual variance (Vollrath 1981;Hasegawa et al 1987;Bhatnagar 1990;Schmidt et al 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that melatonin has, in physiological conditions, a circadian secretory rhythm with low concentrations during daytime and high concentrations at night, with peak concentrations at approximately 0300 h (14). In previous studies, maximum pineal activity has been reported to occur in childhood and progressively decline in the following decades of life (14,15).…”
Section: Discussionmentioning
confidence: 99%